Hamidian Palestine Politics and Society in the District of Jerusalem 1872-1908. - Büssow, J. (The Ottoman Empire and its Heritage, 2011)
During the era of Sultan Abdülhamid II, modern state institutions were established in Palestine, while national identities had not yet developed. Hamidian Palestine explores how the inhabitants of the Ottoman District of Jerusalem interacted with each other and how they organised their interests in a historical moment before 'Arabs' and 'Jews' emerged as the central political categories in the country. Based on a wide range of Arabic, Turkish and Hebrew sources, the book examines the social and political relations of Palestinians from a wide variety of perspectives. By situating individual case studies within larger contexts such as modernisation, regionalisation and state-building, it allows Palestinian society to be compared with other local societies within the Ottoman Empire and beyond.